Factors that intervene into the acquisition process of translation competence: the case of the Language Department at the University of Veracruz - Ortiz Lovillo, Maria del Pilar (Acta Universitaria, 2019)
This paper aims to describe the main points from a qualitative, descriptive, observational and cross-sectional research, which focus on different perspectives about the factors that enable the acquisition of translation competence. This research was carried out during a Bachelor’s Degree in French Language, at the Language Department from the University of Veracruz, during the semester February-June 2007. The main purpose was to determine the level of translation competence in students from the 1990 curriculum. Some results are presented as well as the study’s conclusion.